Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1756286419835708
|View full text |Cite
|
Sign up to set email alerts
|

Outcome, efficacy and safety of endovascular thrombectomy in ischaemic stroke according to time to reperfusion: data from a multicentre registry

Abstract: Background and purpose: In acute ischaemic stroke (AIS) of the anterior circulation (AC) treated with mechanical thrombectomy (MT), data point to a decline of treatment effect with increasing time from symptom onset to treatment. However, the magnitude of the decline will depend on the clinical setting and imaging selection used. The aims of this study were (1) to evaluate the clinical effect of time to reperfusion (TTR); and (2) to assess the safety and technical efficacy of MT according to strata of TTR. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Thrombolysis has shown to improve outcome in selected patients up to 9 h after symptom onset [1], while endovascular thrombectomy lowered disability in selected patients with a large vessel occlusion up to 16-24 h after onset [2,3]. However, for endovascular treatment and thrombolysis [4][5][6] as well as conservative medical management [7] the time from symptom onset to initiation of therapy remains a decisive factor for functional outcome [6]. While efforts to reduce the door-to-treatment time have led to significant improvements [8], the development of prehospital delays in AIS remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombolysis has shown to improve outcome in selected patients up to 9 h after symptom onset [1], while endovascular thrombectomy lowered disability in selected patients with a large vessel occlusion up to 16-24 h after onset [2,3]. However, for endovascular treatment and thrombolysis [4][5][6] as well as conservative medical management [7] the time from symptom onset to initiation of therapy remains a decisive factor for functional outcome [6]. While efforts to reduce the door-to-treatment time have led to significant improvements [8], the development of prehospital delays in AIS remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prior to these RCTs, several studies had challenged the 6-h time window. Some retrospective studies have shown that patients with AIS who had been treated with delayed EVT (>6 h after symptom onset) showed comparable efficacy and safety compared with patients with AIS who had been treated with early EVT (within 6 h after symptom onset) (10,11). These studies provided further evidence for delayed EVT in patients with AIS that needs consideration.…”
Section: Introductionmentioning
confidence: 93%
“…Late presenters have lower rates of successful and excellent reperfusion, higher complication rates and may need increased number of passes during EVT. 118 There is no high-level evidence from RCTs proving efficacy of EVT in extended time windows without advanced neuroimaging. Real-world data from the North American Solitaire Stent Retriever Acute Stroke (NASA) and the Trevo Stent Retriever Acute Stroke (TRACK) registries suggest EVT is equally safe and effective before and after 6 h. 119 …”
Section: Endovascular Treatment In the Anterior Circulation Before And After 6 H From Lswmentioning
confidence: 99%
“…Late presenters have lower rates of successful and excellent reperfusion, higher complication rates and may need increased number of passes during EVT. 118 There is no high-level evidence from RCTs proving efficacy of EVT in extended time windows without advanced neuroimaging. Realworld data from the North American Solitaire Stent Retriever Acute Stroke (NASA) and the Trevo Stent Retriever Acute Stroke (TRACK) registries suggest EVT is equally safe and effective before and after 6 h. 119 The arguments in favor of standard neuroimaging for extended time windows are the following: EVT is both safe and effective; initial studies have shown efficacy but had too restrictive inclusion criteria; relaxing these criteria will increase benefit for more stroke patients, not only those with the most favorable imaging profile.…”
Section: Effective Evt In Advanced Time Windows Without Advanced Neuroimaging: Fact or Fiction?mentioning
confidence: 99%